Annular pancreas in two cases after diamond-shaped anastomosis duodenoduodenostomy: case reports - Ni Luh Gede Wahyuni Suismaya; I Made Kardana; Kadek Deddy Ariyanta (Intisari Sains Medis, 2020)
Background: Annular pancreas is an infrequent congenital disorder characterized as a partial or complete pancreatic tissue around the descending part of the duodenum. Prenatal control is essential in the early detection of the annular pancreas. Initial management might increase better prognosis. We report two cases of the annular pancreas in Sanglah General Hospital, Denpasar, Bali in 2016-2019 to describe the clinical characteristics and outcome of different ages in annular pancreas managed by diamond-shaped duodenoduodenostomy.Case Description: The first case was a six days old baby boy with bile stained vomiting every time he breastfed when she was three days old and got worsen. USG fetal showed polyhydramnios with duodenal or jejunal stenosis. Besides, the abdominal X-ray showed double bubble sign and the laboratory findings were in a standard limit. The second case was a nine months old girl with bile-stained vomiting when she was eight months old and got worsen along with the time. She found with severe malnutrition and mild-moderate dehydration. The laboratory examination revealed electrolyte imbalanced, and abdominal X-ray showed double bubble sign. Postoperative to first feed was 1 day in both cases and full feed duration was 5 and 10 days. Length of stay was 16 and 25 days—both of the cases without complication after surgery.Conclusion: Annular pancreas is a rare congenital malformation that manifests primarily by signs related to duodenal obstruction. Earlier identifications will help to ensure that appropriate treatment can be instigated as soon as possible. Treatment by surgical with duodenoduodenostomy procedure is a surgical technique in the treatment of annular pancreas, with the advances in neonatal intensive care, may reduce the postoperative complications and will make a better outcome.